1995
DOI: 10.1128/jb.177.7.1662-1669.1995
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate cell cycle control of a Caulobacter DNA methyltransferase and the flagellar genetic hierarchy

Abstract: The expression of the Caulobacter ccrM gene and the activity of its product, the M.Ccr II DNA methyltransferase, are limited to a discrete portion of the cell cycle (G. Zweiger, G. Marczynski, and L. Shapiro, J. Mol. Biol. 235:472-485, 1994). Temporal control of DNA methylation has been shown to be critical for normal development in the dimorphic Caulobacter life cycle. To understand the mechanism by which ccrM expression is regulated during the cell cycle, we have identified and characterized the ccrM promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 44 publications
4
84
0
Order By: Relevance
“…The class II flagellar genes have been shown to respond to a DNA replication checkpoint (13,52), in that disruption of DNA replication results in the inhibition of class II flagellar gene transcription. In addition, it has recently been shown that the gene encoding a temporally controlled DNA methyltransferase, which is required for the normal progression of the Caulobacter cell cycle, also responds to a DNA replication checkpoint and has the same promoter structural and functional features as the promoter regions of the class II flagellar genes (51).…”
Section: Vol 177 1995mentioning
confidence: 99%
“…The class II flagellar genes have been shown to respond to a DNA replication checkpoint (13,52), in that disruption of DNA replication results in the inhibition of class II flagellar gene transcription. In addition, it has recently been shown that the gene encoding a temporally controlled DNA methyltransferase, which is required for the normal progression of the Caulobacter cell cycle, also responds to a DNA replication checkpoint and has the same promoter structural and functional features as the promoter regions of the class II flagellar genes (51).…”
Section: Vol 177 1995mentioning
confidence: 99%
“…Further, CcrM in an α-proteobacterium, Caulobacter crescentus, play an important role for cell-type determination mediated by expression of class II flagellar genes. C. crescentus generates two distinct cell types, a motile swarmer cell and a stalked cell (Stephens et al, 1995;Marczynski and Shapiro, 2002). The expression level of CcrM protein controls the amount of transcripts of class II flagellar genes, thereby being related to the development of swarmer cells (Stephens et al, 1996;Wu et al, 1998;Reisenauer et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…ccrM expression is coincident with and sensitive to DNA replication such that if DNA replication is inhibited, CcrM is not produced at high enough levels to overcome Lon degradation (241). Surprisingly, it was found that ccrM is positively regulated by CtrA (202).…”
Section: Regulation Of Dna Replication and Methylation Machinerymentioning
confidence: 99%